Safety and efficiency of the fifth generation Woven EndoBridge device: technical note. (17th January 2019) - Mihalea, Cristian; Caroff, Jildaz; Pagiola, Igor; Ikka, Leon; Hashemi, Gelareh Bani; Naderi, Soheil; Chalumeau, Vanessa; Ples, Horia; Popa, Bogdan Valeriu; Yasuda, Thomas; Marenco de la Torre, Joaquin Jose; Iacobucci, Marta; et al.
Abstract : Backround: The treatment of wide neck bifurcation aneurysms remains challenging despite the introduction of new techniques (Y stenting, waffle cone technique, or flow diverter stents). The Woven EndoBridge (WEB) device is an innovative solution for this type of cerebral aneurysm. A new WEB 17 is now available and has been designed to offer smaller sized devices to optimize navigability and delivery. Methods: Between February 2017 and April 2018 all patients treated with the WEB 17 device in our center were retrospectively reviewed. 25 patients with 28 non-ruptured aneurysms were identified and analyzed. Three patients with two aneurysms both treated with the WEB device were identified. Results: The device was successfully deployed in all cases. Procedure related morbidity was 4% and mortality was 0%. In one case, a delayed postprocedural thromboembolic event occurred owing to device protrusion. Technical success, complications, angiographic outcomes, procedural data, and follow-ups are reported. The modified Rankin Scale score at discharge was 0 for 24 patients (96%). At the 3, 6, or 9 month follow-up, angiograms were taken of 21 of the 25 patients (84%) (24 of 28 aneurysms had been controlled); 3 patients (3 aneurysms) did not receive angiographic follow-up at the time of submission of this work. Complete occlusion was achieved in 22 of 24 aneurysms (91.66%), and 2 of 24 aneurysm (8.33%) showed a neck remnant. Conclusions: The WEB 17 is safe and technically feasible, according to this retrospective single center analysis. For very small bifurcation aneurysms, the WEB 17 seems to have lower complication rates than stent assisted techniques. However, further studies are needed to evaluate the complication rate and long term efficiency.